Merancang Model Pembelajaran Proyek Sains Warga untuk Pendidikan Kesehatan Kerja: Pendekatan Penelitian Berbasis Desain - Asih Luklu Susiati; Andi Asmawati Azis; Abd Muis; Syamsiah Syamsiah; Andi Citra Pratiwi (Biosfer: Jurnal Pendidikan Biologi, 2026)
Occupational Safety and Health (OSH) education requires instructional approaches that integrate scientific understanding with collaborative and contextual learning experiences. However, anatomy and physiology courses are often disconnected from authentic occupational health problems. The present research aimed to design and validate a Citizen Science Project (CSP) learning model for Human Anatomy and Physiology Education within occupational health contexts through a Design-Based Research (DBR) approach. The study involved iterative stages consisting of needs analysis, model design, expert validation, implementation, and evaluation. Collaborative competence was positioned as the primary learning outcome and assessed through structured classroom observations involving undergraduate OSH students. The CSP model integrated five learning stages: mapping, project design, presentation, execution, and gallery walk activities. The findings showed that students demonstrated consistently high collaborative competence across instructional meetings, with mean scores ranging from 81.67 to 85.31 and an overall average of 82.28. Improvements were particularly observed during project execution and reflective dissemination activities. The results indicate that the CSP model effectively promotes collaborative learning and authentic inquiry in Biology Education. These findings contributes to the development of contextual and participatory instructional models that support collaborative competence in occupational health learning.